The Mg isotope signature of marine Mg-evaporites. (15th May 2021) - Shalev, Netta; Lazar, Boaz; Halicz, Ludwik; Gavrieli, Ittai
Highlights: Mg isotope fractionation between evaporated seawater and Mg-salts was determined. 5 Mg-evaporites were studied: Epsomite, Kainite, Carnallite, Kieserite, Bischofite. The fractionation of Kainite and Kieserite is negative and of all others- positive. The impact of the Mg sink in evaporites on seawater δ 26 Mg value is negligible. Mg-evaporites may now serve as an archive for δ 26 Mg of ancient brines and seawater. Abstract: Marine Mg-evaporites are a small oceanic sink of magnesium, precipitating only from extremely evaporated brines. The isotopic composition of Mg in seawater, δ 26 Mgseawater, has recently been shown to be an effective tool for reconstructing the Mg budget of the modern and past oceans. However, estimations of the Mg isotope fractionation between the Mg-evaporites and their precipitating solution are required for full quantification of the isotope effect of the evaporitic sink on δ 26 Mgseawater, as well as for utilizing ancient evaporitic sequences as an archive for past δ 26 Mgseawater . Here, we estimate the Mg isotope fractionation between Mg-evaporites and modern marine-derived brine along the course of seawater evaporation, up to degree evaporation of >200. The sequence of Mg-salts included epsomite (MgSO4 ·7H2 O), kainite (KMgClSO4 ·3H2 O), carnallite (KMgCl3 ·6H2 O), kieserite (MgSO4 ·H2 O) and bischofite (MgCl2 ·6H2 O). The following isotope fractionation values, either negative or positive, were calculated from the isotope difference between the salt and its precipitating brine, and from the evolution of δ 26 Mg in the brine throughout the evaporation: Δcarnallite-brine = +1.1‰, Δepsomite-brine = +0.59‰, Δbischofite-brine = +0.33‰, Δkieserite-brine  = −0.2‰ and Δkainite-brine  = −1.3‰. Magnesium isotopic compositions determined on minerals from different ages in the geological record corroborate well these results. Due to precipitation of multi-mineral assemblages having isotope fractionation values of opposing signs, the δ 26 Mg value of the brine changes only slightly (<0.5‰) throughout the evaporation path, despite the considerable Mg removal (>50%). The isotope fractionations are shown to correlate with the number of water molecules coordinated to the Mg 2+ and with Mg-O bond length in the mineral lattice. Given these isotope fractionations, it is calculated that a volume of 0.4 · 10 6 –0.8 · 10 6 Km 3 of a mono-mineral assemblage of kainite or carnallite needs to precipitate in order to change seawater δ 26 Mg by only 0.1‰. This huge volume is by far larger than the volume of these minerals known to date in the global geological record. Therefore, it is concluded that the impact of Mg-evaporites formation on δ 26 Mgseawater has been insignificant since the Proterozoic. The results of this study suggest that the Mg isotopic composition of Mg-evaporites preserved in the geological record of evaporitic basins may be used to: 1) quantify geochemical processes that fractionate Mg-isotopes within these basins, such as dolomitization; and 2) complete the secular variations curve of the marine δ 26 Mg record using basins with well-established evaporitic sequences.